(untitled) (Scientific journal of the Fergana State University, 2024)
The influence of various food plants on the development and morphological characteristics of Mythimna unipuncta has been studied. Indicators, morphometric features and coefficient of variation of the Mythimna unipuncta caterpillar feeding on Zea mays, Capsicum annuum, Rumex confertus differ. In this regard, the quality and physical properties of food plants are of particular importance. All morphometric indicators of Mythimna unipuncta caterpillars developed on corn are higher than those of sorrel samples, and they also differ in a high degree of pupal formation and development of butterflies from them. Despite this, the sorrel plant is important for the survival of phytophages during periods of nutrient shortage.